The Malay Mail, 22 Oktober 2008 (The New Straits Times Press (M) Bhd, 2008)
Economic inequality is growong in the world's richest countries, particularly in the United States, joepardising the American dream of social mobility just as the world tilts toward recession, a 30-nation report said yesterday.